Christendom: The Triumph of a Religion, AD 300-1300. By Peter Heather. New York: Alfred A. Knopf, 2023. xxiv + 704 pp. $ 40.00 cloth - Noble, Thomas F. X. (Church history, 2024)
Christendom: The Triumph of a Religion, AD 300-1300. By Peter Heather. New York: Alfred A. Knopf, 2023. xxiv + 704 pp. $ 40.00 cloth. - Volume 93 Issue 3.